RANCANG BANGUN APLIKASI MONITORING JARINGAN METRO ETHERNET STUDI KASUS PADA PT. TELKOM WILAYAH SEMARANG (Information Technology and Telematics, 2016)
A communication needs of internet,TV media,phone in today's global era is very important in supporting our daily activities.It requires a high technology device to overcome the number of customer service traffics.One of the technologies that support for large scale comprehensive services is Metro Ethernet. Metro Ethernet has been established as a  Single Platform IP Transport for all Telkom Group services that it has an important role and strategic.With this application,can help us to monitor and check the condition of the device status via web without going through the Command Line Interface. Keyword : Metro Ethernet, Monitoring, PT Telkom Semarang